P09 Initial diagnostic outcome of screening for congenital hypothyroidism after newborn bloodspot screening: a uk surveillance study. (27th April 2015) - Knowles, RL; Oerton, JM; Dezateux, C; Butler, G; Griffiths, P; Tetlow, L; Cavanagh, C; Cheetham, T
Abstract : Introduction: Primary congenital hypothyroidism (CHT) is due to reduced thyroid hormone production. Oral thyroxine therapy commenced soon after birth improves cognitive development and growth. Despite 30 years of newborn screening for CHT in the UK, its success in identifying babies who require lifelong therapy for CHT remains unclear. Aim: To determine, through UK-wide active surveillance, the number and characteristics of children aged ≤5 years diagnosed annually with CHT, detected by screening or after clinical manifestations, and to describe clinical management. Results: During 13 months of surveillance, 704 children with positive screening results were reported by screening laboratories. Local clinicians completed 643 questionnaires (response rate = 91%). An additional 20 children aged <5 years were notified who were not identified through screening, including three diagnosed prior to screening (2 family history, 1 unwell) and 17 with negative screening tests (10 preterm, 5 unwell, 2 Downs syndrome); screening results were untraceable for 2 children. Of 643 screen positive children, 260 (40%) were boys, 130 (20%) were <37 weeks gestation and most were of white or Asian ethnicity (379[59%] and 133[21%] respectively). Investigations carried out soon after referral demonstrated serum TSH >40 mU/l in 365; in an additional 43 children an abnormal thyroid scan result was associated with serum TSH ≤40 mU/l. Based on the reported initial investigations for 643 children, an expert panel assigned a diagnosis of CHT in 410, excluded CHT in 120 and considered 113 had probable/possible CHT requiring follow-up. The local clinicians commenced 485 children on oral thyroxine, 401 of whom were assigned as having definite CHT by the expert panel. During 12 months of follow up after diagnosis, eleven children died of causes unrelated to CHT. Conclusion: Our findings suggest that the predictive value of a positive screening test is at most 81% (523/643) assuming CHT is confirmed in those with possible CHT as an initial diagnosis. Our data suggest that permanent CHT cannot be confirmed at initial diagnostic investigation in a significant proportion of screen positive babies. Follow up of this cohort is continuing to determine outcome by two years of age. Funding: Public Health England (NHS Newborn Blood Spot Screening Programme).